Investigation of factors affecting the green synthesis of silver nanoparticles from guava leaf extract - Dong Duc Tran; Van Hoang Bui; Quang Nguyen Dinh; Duc Cuong Nguyen; Cong Trinh Bui; Thao Vu Thi (Vietnam Journal of Science, Technology and Engineering)
Green-synthesised silver nanoparticles offer substantial advantages for biomedical applications due to reduced chemical impacts, straightforward methods, and environmental friendliness. However, the outcome of nanoparticle synthesis is heavily influenced by reaction conditions, affecting their formation, size, and properties. It is therefore crucial to establish precise synthesis protocols and optimise conditions pertaining to reducing agents, silver salt concentration, and other influential factors. This study identifies optimal conditions for the green synthesis of silver nanoparticles using guava leaf extract. Various analytical techniques such as Ultraviolet-visible spectroscopy (UV-Vis), Dynamic light scattering (DLS), X-ray diffraction (XRD), Field-emission scanning electron microscopy (FE-SEM), Fourier-transform infrared spectroscopy (FT-IR), and Energy-dispersive X-ray spectroscopy (EDX) were employed to characterise the material properties. The synthesised silver nanoparticles exhibited absorption at 430 nm wavelength, demonstrated a face-centred cubic crystalline structure with high crystallinity, and showed an average particle size ranging from 30-40 nm, predominantly spherical and uniformly distributed. Flavonoids present in the guava leaf extract were identified as the primary compounds responsible for the reduction of silver ions. To minimise residual extract and enhance the applicability of silver nanomaterials, a washing and filtration process was implemented. A thorough investigation into influencing factors and the resolution of issues related to the green synthesis of silver nanoparticles can pave the way for future research and boost the commercial potential of green nanomaterial products for medical and environmental applications.